Magmatic Evolution of Dago Volcano, West Java, Indonesia - Adimedha, Tyto Baskara; Harijoko, Agung; Handini, Esti; Sukadana, I Gde; Syaeful, Heri; Ciputra, Roni Cahya; Rosianna, Ilsa; Indrastomo, Frederikus Dian; Pratiwi, Fadiah; Rachael, Yoshi (Badan Riset dan Inovasi Nasional, 2023)
Dago Volcano is a product of Miocene Sunda Arc volcanism located southeast of the capital city of Jakarta. The morphological change from flat lava flow to steeper lava morphology implies a process of magma evolution under Dago Volcano. This research provides an overview of the magma evolution that occurs on this volcano. The methods used include volcanostratigraphic analysis, petrographic analysis, mineral chemistry, and whole-rock geochemistry. The volcanostratigraphy of Dago Volcano is composed of two eruption centers and a flank eruption forming lava and cinder cones products. The mineralogical associations of Dago Volcano products include plagioclase, olivine, and clinopyroxene. The mineral textures of Dago edifices show zoning, sieve, and reaction rims textures. Geochemically, the Dago Volcano product has a magma affinity of med-K calc-alkaline with quite high levels of MgO, Ni, and Cr approaching the characteristics of primitive magma. The magma evolution process of Dago Volcano includes fractional crystallization and magma mixing which originates from the same magma source.